2016
DOI: 10.1007/s40268-016-0131-2
|View full text |Cite
|
Sign up to set email alerts
|

Dual Bronchodilator Therapy with Umeclidinium/Vilanterol Versus Tiotropium plus Indacaterol in Chronic Obstructive Pulmonary Disease: A Randomized Controlled Trial

Abstract: IntroductionThe fixed-dose, long-acting bronchodilator combination of umeclidinium/vilanterol (UMEC/VI) has not previously been compared with a combination of a long-acting muscarinic antagonist and long-acting β2-agonist in patients with chronic obstructive pulmonary disease (COPD).MethodsThis 12-week, randomized, blinded, triple-dummy, parallel-group, non-inferiority study compared once-daily UMEC/VI 62.5/25 mcg with once-daily tiotropium (TIO) 18 mcg + indacaterol (IND) 150 mcg in patients with moderate-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 17 publications
(27 reference statements)
1
14
0
1
Order By: Relevance
“…However, a subsequent direct comparison of TIO ? IND with UMEC/VI found no significant difference in rescue medication use [44].…”
Section: Weeksmentioning
confidence: 80%
“…However, a subsequent direct comparison of TIO ? IND with UMEC/VI found no significant difference in rescue medication use [44].…”
Section: Weeksmentioning
confidence: 80%
“…Clinical trials of the fixed‐dose LABA/LAMAs reported similar or lower frequencies of exacerbations compared with the monotherapy arms . There have been relatively few comparative studies of LABA/LAMA and LABA/ICS efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of the fixed-dose LABA/LAMAs reported similar or lower frequencies of exacerbations compared with the monotherapy arms. 19,21,[26][27][28] There have been relatively few comparative studies of LABA/LAMA and LABA/ ICS efficacy. One study compared the lung function of a LABA/LAMA and LABA/ICS in the short term; this was a 6-week randomized trial demonstrating that the 12-hour lung function profiles of patients receiving a combination of tiotropium/formoterol were significantly better than those receiving combination salmeterol/fluticasone (as measured by FEV 1 area under the curve [AUC][0-12], forced vital capacity [FVC] AUC[0-12], peak FEV 1 , and peak FVC).…”
Section: Discussionmentioning
confidence: 99%
“…Each combination had undergone a specific development program and clinical trial testing to assess its efficacy and safety for patients with COPD. Unfortunately, no direct head-to-head comparison of the available combinations has been performed yet, the only exception being a clinical trial assessing tiotropium/indacaterol versus UMEC/VIL 7. The results of this study indicated similar improvements in lung function and patient-reported outcomes over a 12-week period, with comparable tolerability and safety profiles 7…”
Section: Introductionmentioning
confidence: 84%